(untitled) (E Global Congress, 2025)
Over the period 2015–2025, obstructive pulmonary diseases have maintained high medical and social significance, remaining among the leading causes of ambulance calls and hospitalizations. The analysis included ambulance service data for the city of Tashkent over the first six months of 2025. Of 16,827 total calls, 2,478 (14.7%) were related to dyspnea attacks. Women accounted for 58% (n=1,442) and men for 42% of cases. The largest proportion of calls occurred in patients aged 60–75 years. These data reflect a significant burden on emergency medical services and emphasize the need for unified pre-hospital management protocols for patients with bronchial obstruction and stronger coordination between emergency and pulmonology services.